Epidemiological and virological differences in human clustered and sporadic infections with avian influenza A H7N9. (August 2016) - Wu, Zuqun; Sha, Jianping; Yu, Zhao; Zhao, Na; Cheng, Wei; Chan, Ta-Chien; Amer, Said; Zhang, Zhiruo; Liu, Shelan
Highlights: The epidemiology and virology of human family cluster infection cases (FCs), live bird market cluster infection cases (LCs), and sporadic cases with avian influenza A H7N9 virus were compared, focusing on the difference in primary and secondary cases.. There was no difference in the case fatality rate between FCs and LCs; the human-to-human transmission capability in the two groups was limited and not sustained. Average age, comorbidities, exposure to birds, and H7N9-positive rate were the most detrimental factors in FCs and LCs. The percentage of mild cases was much higher in secondary cases than in primary cases for FCs. However, no difference was found between the two groups in LCs. FC and LC strains shared 99.1–99.9% homology and increased human adaptation. Summary: Background: Previous research has suggested that avian influenza A H7N9 has a greater potential pandemic risk than influenza A H5N1. This research investigated the difference in human clustered and sporadic cases of H7N9 virus and estimated the relative risk of clustered infections. Methods: Comparative epidemiology and virology studies were performed among 72 sporadic confirmed cases, 17 family clusters (FCs) caused by human-to-human transmission, and eight live bird market clusters (LCs) caused by co-exposure to the poultry environment. Results: The case fatality of FCs, LCs and sporadic cases (36%, 26%, and 29%, respectively) did not differ among the three groups ( p  > 0.05). The average age (36 years, 60 years, and 58 years), co-morbidities (31%, 60%, and 54%), exposure to birds (72%, 100%, and 83%), and H7N9-positive rate (20%, 64%, and 35%) in FCs, LCs, and sporadic cases, respectively, differed significantly ( p  < 0.05). These higher risks were associated with increased mortality. There was no difference between primary and secondary cases in LCs ( p  > 0.05). However, exposure to a person with confirmed avian influenza A H7N9 (primary 12% vs. secondary 95%), history of visiting a live bird market (100% vs. 59%), multiple exposures (live bird exposure and human-to-human transmission history) (12% vs. 55%), and median days from onset to antiviral treatment (6 days vs. 3 days) differed significantly between primary and secondary cases in FCs ( p  < 0.05). Mild cases were found in 6% of primary cases vs. 32% of secondary cases in FCs ( p  < 0.05). Twenty-five isolates from the three groups showed 99.1–99.9% homology and increased human adaptation. Conclusions: There was no statistical difference in the case fatality rate and limited transmission between FCs and LCs. However, the severity of the primary cases in FCs was much higher than that of the secondary cases due to the older age and greater underlying disease of the latter patients.